Modern Yoga Practice and Human Rights as Reflexive, Embodied Experience - O'Hare, Kathleen (Curtin University, 2017)
This is qualitative research that explores the recent, observable intersection of yoga and activism in Australia and the US. I utilise case studies of yoga practitioners and activists to understand the way in which modern yoga, has intersected with contemporary human rights to become an observable example of engaged yoga. The findings establish that engaged yoga is comprised of a number of components which are categorised into two main areas: self-responsibility and meaningful actions.